Sobre fibrados e poliedros de dimensão finita - Bautista, Kevin Moradel (2021)
The objective of this work is to establish the existence of universal bundles and to relate this existence to finite dimension polyhedra. As a consequence, we present examples of universal bundles for the case of classic groups.